2014
DOI: 10.2334/josnusd.56.215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the smear layer on apical seals produced by two calcium silicate-based endodontic sealers

Abstract: We compared the apical seals of two new calcium silicate-based sealers (iRoot SP and MTA Fillapex) in the presence and absence of a smear layer. Eighty-two human premolars were prepared and randomly divided into four groups. In groups 1 and 3, the smear layer was retained. In groups 2 and 4, the root canals were irrigated with EDTA to remove the smear layer. Canals were filled using gutta-percha/iRoot SP (in groups 1 and 2) or obturated with gutta-percha/MTA Fillapex (in groups 3 and 4). Fluid filtration was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
10
0
4
Order By: Relevance
“…In this method, the sealing ability is measured via air bubble movement within a capillary tube (21,55-58), consisting of an obturated canal with its coronal portion connected to a tube filled with water at atmospheric pressure, and its apex connected to a 20-μL glass capillary tube measuring 170 mm in length and with a uniform caliber filled with water. A pressure of 0.1 atm is applied through the coronal part, forcing the water through the empty spaces along the root canal (53).…”
Section: Resultsmentioning
confidence: 99%
“…In this method, the sealing ability is measured via air bubble movement within a capillary tube (21,55-58), consisting of an obturated canal with its coronal portion connected to a tube filled with water at atmospheric pressure, and its apex connected to a 20-μL glass capillary tube measuring 170 mm in length and with a uniform caliber filled with water. A pressure of 0.1 atm is applied through the coronal part, forcing the water through the empty spaces along the root canal (53).…”
Section: Resultsmentioning
confidence: 99%
“…Trabalhos avaliando as propriedades do iRoot SP necessárias para uma melhor vedação do canal radicular, o compararam a outros cimentos endodônticos, mostrando que o iRoot SP permitiu maior selamento apical do que o Sealapex, o EndoREZ e o MTA Fillapex. 34,35 Estudos são contraditórios, um menciona não existir diferença significativa entre o iRoot SP e o AH Plus, 34 porém outro aponta que o EndoSequence BC Sealer apresenta maior vedamento do que o AH Plus. 12 Em relação à interferência do smear layer na propriedade de vedamento e resistência de união do BC Sealer, resultados similares foram obtidos, a ausência ou presença do smear layer não interferiu em nenhuma destas propriedades.…”
Section: Resultsunclassified
“…These qualities ensure a high closure for the cover [17]. In addition, it has been shown that the presence or absence of a smear layer does not affect the adherence to the canal wall [18].…”
Section: Discussionmentioning
confidence: 99%